The Impact of political interference on the quality of infrastructural delivery of projects in the Free State - Godongwana, Athenkosi (University of the Witwatersrand, Johannesburg, 2024)
Political interference has always been a point of criticism in infrastructure development projects in the Free State. Such interference has a significant influence on project delivery quality, as it frequently causes delays, cost overruns, and substandard results. This article examines the different ways in which political interference impairs the proper implementation of infrastructure projects in the Free State. The purpose of this enquiry was to firmly establish, if any the role that political interference plays in the quality of infrastructure that is provided in the Free State. The study evaluated for key aspects that affect the quality of infrastructure development in the Free State, namely: irregular service provider appointments, irregular employment practices, cost overruns and programme delays, poor quality infrastructure. The study employed qualitative as well as quantitative (mixed) data collection methods. The qualitative aspect entailed primarily the use of questionnaires on a random sample of officials that are in executive public offices in government departments. These questionnaires were open ended to allow participants to add in or motivate their initial responses. The Quantitative consisted of systematic interviews, measurements and observations, and records or document reviews for information that was measurable. The study found that factors that negatively influence the quality of infrastructure delivery in local government include: a) Political interference b) Institutional incapacity c) An insufficient quality monitoring systems Amongst other findings, the study found that government officials are regarded to be the most active in corrupt operations as customers, contractors, and subcontractors. Contract granting for political advantage, nepotism and conflicts of interest, and meddling in the tender award 2 process are the most common forms of corruption linked with government employees. Corruption is particularly frequent during the project's bid appraisal and tendering phases.
A research report submitted in fulfillment of the requirements for the Master of Business Administration, In the Faculty of Commerce, Law and Management, School of Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Political interference; Quality of infrastructure; SDG-9: Industry, innovation and infrastructure